Spanish Poetry translated into English: the case of "England's Helicon" - Chamosa, José Luis (SEDERI: yearbook of the Spanish and Portuguese Society for English Renaissance Studies, 1990)
Pastoral literature and its world of archetypes are very far away from the present day sensibility and it is hardly easy to understand how such a stereotyped production was ever thought to be the touchstone of a writer´s talent and capacity.